TINJAUAN PENGUMUMAN LELANG EKSEKUSI HAK TANGGUNGAN (STUDI KASUS DI KPKNL YOGYAKARTA) - , RISKA ADIAWAN YULANDA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to determine the suitability of the implementation of the announcement auction execution of liability at State Assets and Auction Services Office in Yogyakarta by Finance Minister Regulation number. 93/PMK.06/2010 on Auction Guidelines and cancellation of the auction after the auction announcement at the office of state property and auction services Yogyakarta. This research is empirical juridical material library research and field research. Field collection as the primary done with the interview guidelines. While the literature as supporting data in this research conducted with library research. The results obtained were analyzed qualitatively and maked in the form of descriptive. The results showed that 1) Implementation of the announcement auction made by the seller/applicant auction at the State Assets and Auction Services Office in Yogyakarta's not all according to the ministers of finance regulation number 93/PMK.06/2010, still there are errors regarding the content of the editorial, however in practice never be corrected the auction announcement. 2) The cancellation of the auction after the auction announcement of the execution mortgage at State Assets and Auction Services Office in Yogyakarta, because